MAKNA NILAI PENTING BUDAYA KEANEKARAGAMAN HAYATI TUMBUHAN BAGI MASYARAKAT DI TAMAN NASIONAL KERINCI SEBLAT DI KABUPATEN KERINCI, PROPINSI JAMBI [The Importance of Cultural Significance Index of Plants Diversity For The Communities Within The Kerinci Seblat National Park, Kerinci Regency, Province of Jambi] - Helida, Asvic; Zuhud, Ervizal A.M.; Hardjanto, Hardjanto; Purwanto, Y.; Hikmat, Agus (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Index of Cultural Significance biodiversity plants in ethnobotanical study was an important step for seeking a strategy for subsisten activity. This study was aimed to identify utilised plants that have the highest value at Kerinci community. The current study was conducted in three villages within the Kerinci Regency, Jambi Province, which located close to the Kerinci Seblat National Park: Baru Lempur, Lama Tamiai, and Ulu Jemih for 8 months (October 2013 to May 2014). Data was obtained by implementing Â participation-observation method through interviews. Estimation of cultural significance for every plant species observed using the Index for Cultural Significance (ICS). Results indicated that the people of Kerinci possessed good knowledge on the biodiversity of their surrounding. Two hundred and thirty four species of useful plants we recorded with ICS value ranging from 3 to 59. Rice (Oryza sativa; Poaceae) and Cinnamon (Cinnamomum burmannii; Lauraceae) had highest ICS value, whereas âingguâ (Ruta angustifolia; Rutaceae) and âbunching onionâ (Allium fistulosum, Amaryllidaceae ) have the lowest ICS value.